2014
DOI: 10.7556/jaoa.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking Behaviors of Osteopathic Medical Students

Abstract: Multitasking during lecture is prominent among medical students, and examination schedule is the most influential factor. Although a robust drop in mean score on a lecture-based, unannounced quiz was identified 1 day before a scheduled examination, the effect from multitasking on this process remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…By contrast, socializing with fellow students and friends was evaluated as being equally important during lectures. Likewise, Shah et al reported that among American osteopathic medical students, a large proportion of time spent during lectures was used to study for other classes or was spent on social media or reading emails [ 32 ]. The benefits of compulsory attendance with or without being physically present in a lecture hall are, therefore, questionable.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, socializing with fellow students and friends was evaluated as being equally important during lectures. Likewise, Shah et al reported that among American osteopathic medical students, a large proportion of time spent during lectures was used to study for other classes or was spent on social media or reading emails [ 32 ]. The benefits of compulsory attendance with or without being physically present in a lecture hall are, therefore, questionable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, medical students reported little interest and low presence at face-to-face lectures before the COVID-19 pandemic [39]. Accordingly, in a survey among American osteopathic students, a large proportion of time spent during face-to-face lectures was used to study for other classes or was spent on social media or reading emails [44]. We hypothesize that the teaching coordinators in our study differentiated-similar to the medical students-between the requirements of small-group learning in interactive seminars and the passive delivery of information during lectures.…”
Section: Plos Onementioning
confidence: 99%